1992
DOI: 10.1002/j.1460-2075.1992.tb05363.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory mother cell division is specifically affected in a Cyclin-A mutant of Drosophila melanogaster.

Abstract: Cyclin proteins are one of the important components of the mechanism regulating mitosis in eukaryotic cells. We isolated a Drosophila Cyclin‐A mutant in which the progenitor cells of the peripheral nervous system (the sensory mother cells) do not divide properly, causing the loss and other abnormalities of mechanosensory organs in the adult fly. Sequence analysis of the mutant genome reveals that a P element is inserted into the first intron of the Cyclin‐A gene. A 13 kb wild‐type genomic DNA containing the Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…We also note that the cln3 A‐10 mutation overlaps the region of the Cln3 HPD (Figure 1). These charged residues were not mutated in the original studies characterizing the HPD in mammalian cyclin A (Schafer et al , 1989; Ueda et al , 1992; Schulman et al , 1998; Cross and Jacobson, 2000). Similar to results seen with the Cln3‐hpm mutation of cln3 ‐A10 shows a defect in the cln − bck2 − viability assay at elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…We also note that the cln3 A‐10 mutation overlaps the region of the Cln3 HPD (Figure 1). These charged residues were not mutated in the original studies characterizing the HPD in mammalian cyclin A (Schafer et al , 1989; Ueda et al , 1992; Schulman et al , 1998; Cross and Jacobson, 2000). Similar to results seen with the Cln3‐hpm mutation of cln3 ‐A10 shows a defect in the cln − bck2 − viability assay at elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggested that rcal and cyclin A function in a common pathway: (1) the embryonic cell cycle phenotypes of cyclin A and rcal are similar; (2) rca I and cyclin A suppress both the meiotic and mitotic rux phenotypes; and (3) rcal is a dominant enhancer of a viable allele of cyclin A, cyclin A h~ (Ueda et al 1992; 98 data not shown). To gain insight into the function of rcal, we characterized it in more detail.…”
Section: Rcal Encodes a Novel Proteinmentioning
confidence: 99%
“…Cyclin A is known to be required for SOP cell divisions and it has been proposed that proneural factors regulate its expression by binding to an element in its first intron [24]. Loss of one copy of the cyclin A gene resulted in suppression of Ch neuronal duplication in cato homozygote embryos (55% of segments with duplicated v'ch1 neurons, n = 42).…”
Section: Resultsmentioning
confidence: 99%